Studies on mosquitoes (Diptera: Culicidae) and anthropic environment: 7- Behaviour of adults Nyssorhynchus anophelines with special reference to Anopheles albitarsis s.l. in South-Eastern Brazil - Forattini Oswaldo Paulo; Kakitani Iná; Massad Eduardo; Marucci Daniel (Universidade de São Paulo, 1995)
Results obtained with catches performed at several sites of the Ribeira Valley, SP (Brazil) are reported. Collections with Shannon type traps showed a concentration of An.albitarsis s.l. in the Experimental Farm of Pariquera-Açu County, associated with the development of irrigated rice cultivation. Two species of the complex, named A and B, were recognized. Species B predominated in the samples. Indoor and outdoor crepuscular human bait captures were performed a the domiciliary environment. The two species showed a generally low William's media valve of 0.2, the highest value obtained was 1.6. No differences were found between indoor and outdoor behaviours between the two species of the complex.